Accelerate Pembelajaran Al-Qur’an Berbasis Neurologi (Pola Metode Al-Barqy dan Wafa) - Thoifah, I’anatut (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Abstract. This study aims to determine the pattern of neurology-based learning methods of Al-Qur'an Al-Barqy and wafa as an effort to synchronize these methods with the principles of accelerated learning required in this advancement era. Researchers Use research methods library research or commonly referred to as literature studies by collecting primary and secondary data related to al-Barqy and death methods, then analyzing neurology using descriptive analysis. The results of this study indicate that the method of learning al-Qur'an al-barqy and wafa with its unique characteristics includes functioning of the right and left brain, besides being simple, fun and effective and making it easier for students to remember and recall old memories easily are points. It is important to acceleratinglearning neurology-based with the acrostic mnemonic method, where the language used is the daily language of students such as Ma-Ta-Sa-Ya and A-Da-Ra-Ja.